Effects of culture conditions on the size, morphology and wet density of spores of Bacillus cereus 569 and Bacillus megaterium QM B1551. (30th May 2017) - Xu Zhou, K.; Wisnivesky, F.; Wilson, D.I.; Christie, G.
Abstract: The influence of variable culture conditions on the size and wet density of spores of Bacillus cereus and Bacillus megaterium were examined in this work. Culture temperature and initial pH was shown to have a significant impact on the size of both species, with increasingly alkaline culture media and elevated culture temperatures resulting in spores that were, on average, up to 25% reduced in volume. Increasing concentrations of inorganic salts in sporulation media exerted differing effects on each species; whereas a fivefold increase in the concentration of all salts resulted in only minor differences to the dimensions of B. cereus spores, B. megaterium spores became more elongated, displaying an average increase in volume of almost 30%. Similarly, as the spore elongated to yield aspect ratios larger than 1·4, their shape changed from typical prolate spheroids to cylinders with hemispherical ends. In contrast with previous studies, culture conditions employed in this study exerted no discernible impact on the wet density of B. cereus or B. megaterium spores. Significance and Impact of the Study: Bacterial spores of the genera Bacillus and Clostridium represent nature's most durable cells in terms of their extreme resistance to a variety of deleterious environments. As a result, they are of concern in the food processing, healthcare and other sectors, and are of increasing biotechnological interest. Improved understanding of variance in spore size, morphology and density may aid the development of certain spore‐associated applications (e.g. spore surface display) while contributing to active areas of research such as spore adhesion and resistance to heat. Abstract : Significance and Impact of the Study: Bacterial spores of the genera Bacillus and Clostridium represent nature's most durable cells in terms of their extreme resistance to a variety of deleterious environments. As a result, they are of concern in the food processing, healthcare and other sectors, and are of increasing biotechnological interest. Improved understanding of variance in spore size, morphology and density may aid the development of certain spore‐associated applications (e.g. spore surface display) while contributing to active areas of research such as spore adhesion and resistance to heat.